Financial Literacy Analysis of Brick Business Actors in Bontotangnga Village, Bajeng District, Gowa Regency - Muh. Yahya; Andi Naila Quin Azisah Alisyahbana; Ilham Abu; Rizka Aisyah Nurjannah (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This study aims to determine the financial literacy of brick business actors in Bontotangnga Village, Bajeng District, Gowa Regency. This study uses a qualitative approach to the type of phenomenological research. Data collection techniques were carried out by interviews, observation, and documentation. The results of the study show that each entrepreneur has not utilized the services and products of existing financial institutions. Even though the services of financial institutions will greatly assist busi ness transactions and can facilitate the expansion of sales. The results of this study found that the opening of a brick business was due to the basic factors inherited from their parents' business. Brick entrepreneurs are also influenced by suppliers of raw materials, so that output and fluctuations in raw materials will affect production costs which ultimately reduce profits, especially for brick entrepreneurs who do not record income and expenses in their business activities.